Bird’s-eye view of per- and polyfluoroalkyl substances pollution research in the African hydrosphere - Sabastian Simbarashe Mukonza; Nhamo Chaukura (npj Clean Water)
Abstract The surge in Africa’s economy has led to increased use of per- and polyfluoroalkyl substances (PFASs), resulting in environmental pollution. This has spurred regulatory and research efforts to mitigate these impacts. We used data analytics to study PFAS pollution in aquatic ecosystems in Africa and model PFAS concentrations using socio-economic variables. In agreement with literature, urbanization, gross domestic product, and population growth drive PFAS pollution.